2003
DOI: 10.1039/b300158j
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of chlorine by glow discharge quadrupole mass spectrometry in Zr–2.5Nb alloys

Abstract: Direct determination of chlorine in Zr-2.5Nb alloys down to parts per billion levels has been carried out by use of a glow discharge quadrupole mass spectrometer (GD-QMS). The 35 Cl isotope was used for quantification. The relative sensitivity factor (RSF) for chlorine in zirconium matrix (with a 35 Cl isotope) was determined using a zirconium matrix standard disc of known concentration of chlorine (155 ¡ 5 mg kg 21 ) determined by turbidimetry. The concentrations of chlorine obtained using GD-QMS and by pyroh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 2 publications
1
18
0
Order By: Relevance
“…The discharge voltage at 1.2 kV resulted in a maximum ion intensity at constant discharge current of 3.0 mA for both matrices (6 · 10 5 ions s À1 for 90 Zr + ion for Zr matrix and 3 · 10 5 ions s À1 for 56 Fe + ion for Fe matrix samples). Earlier it was also observed that the same discharge parameters resulted in sufficient signal intensity for chlorine present at ultra-trace levels along with high signal intensity for zirconium in Zr-2.5%Nb alloys [9]. Our experiments on other Zr-based samples (metals, Zircaloys) also showed that the same discharge parameters resulted in maximum matrix intensity along with sufficient signal for boron.…”
Section: Discharge Parameterssupporting
confidence: 67%
See 2 more Smart Citations
“…The discharge voltage at 1.2 kV resulted in a maximum ion intensity at constant discharge current of 3.0 mA for both matrices (6 · 10 5 ions s À1 for 90 Zr + ion for Zr matrix and 3 · 10 5 ions s À1 for 56 Fe + ion for Fe matrix samples). Earlier it was also observed that the same discharge parameters resulted in sufficient signal intensity for chlorine present at ultra-trace levels along with high signal intensity for zirconium in Zr-2.5%Nb alloys [9]. Our experiments on other Zr-based samples (metals, Zircaloys) also showed that the same discharge parameters resulted in maximum matrix intensity along with sufficient signal for boron.…”
Section: Discharge Parameterssupporting
confidence: 67%
“…Hence the minimum 40 min of pre-sputter time was required to obtain a stable signal for boron determination using GD-QMS technique. In our earlier work [9] for chlorine in zirconium matrix, minimum 50 min of pre-sputter time was found to be essential. In general, elements of higher concentration require less pre-sputter time (20-30 min) only.…”
Section: Studies On Stabilisation Time For Boron Determinationmentioning
confidence: 97%
See 1 more Smart Citation
“…PH-IC has been used for the determination of chlorine in nuclear fuels and various material like aluminum foil, Whatman filter paper, surgical gloves, methanol and tetrachloroethelene that were used during fuel fabrication process [4,5]. Chlorine was determined in nuclear fuel by pyrohydrolysis coupled with spectrophotometry [6], while glow discharge mass spectrometry has been used to measure chlorine in Zr-2.5Nb alloys [7].…”
Section: Introductionmentioning
confidence: 99%
“…# Present address: Physics Department, Faculty of Science, The M.S. University of Baroda, Vadodara -390002, India (DPCSV) [7], glow discharge quadruple mass spectrometry (GD-QMS) [8,9], spark source mass spectrometry (SSMS) [10], low-energy deuteron activation analysis and neutron activation analysis [11,12]. Among these, the turbidimetric method [3] is one of the classical methods and is used for the estimation of chlorine concentration in the range of 20-200 µg/g.…”
Section: Introductionmentioning
confidence: 99%